THE DEVELOPMENT OF THE READING CULTURE AMONG THE YOUTH - Kdirbaeva, G.; Orazgalieva, A. (FAN va JAMIYAT, 2018)
The article deals with the concepts of reading and reading culture, their meanings, as well as strategies for developing of reading and reading culture among the youth. The author fulfils the task to study the roles of libraries, librarians and teachers in developing reading culture. There are given ideas of the foreign scholars and some practical conclusions of the research works on the investigated topic.